Computer visual syndrome in medical students in virtual education of a Peruvian university during 2021: Síndrome visual informático en estudiantes de medicina en educación virtual de una universidad peruana durante el 2021 - Meneses Castañeda, Rosario Mercedes (2023)
Introduction: During virtual classes in the context of COVID-19, students were exposed to digital screens for many hours, so they could present computer vision syndrome. Objective: To determine the frequency of computer vision syndrome in sixth-year medical students at Ricardo Palma University during virtual education due to COVID-19 in October and November 2021. Methods: Cross-sectional descriptive study in 147 sixth-year medical students who received virtual education at a Peruvian university during 2021. A non-probability sampling was used for convenience and the SVI was evaluated with the SVI-Q questionnaire, in addition characteristics were evaluated. demographics, visual preventive measures and eye diseases. The results were analyzed with SPSS v.21 for Windows. The study was approved by the Ethics Committee. Results: Most of the students were young adults (54%) and female (60%). The frequency of computer vision syndrome was 93%, it occurred in (94%) women and (90%) men. Most of the students reported having myopia (44%) and astigmatism (22%). The most common visual symptoms were tearing (7.9%), itching (7.6%) and headache (7.6%). Conclusions: A high frequency of SVI was found in medical students who took virtual classes.